Causes of mortality among wild swans in Britain - Brown, Martin J; Linton, Emma; Rees, Eileen C (Wildfowl, 1992)
Post mortem data from 366 dead swans recovered from the wild between 1951 and 1989 were examined. The main causes of death were flying accidents (accounting for 22% of adult deaths and 23% of juveniles), lead poisoning (in 21% of adults and 10% of juveniles), trauma (in 8.4% of adults, 8.7% of juveniles and 30% of Mute Swan downies), tuberculosis (6.0% of adults and 1.0% of juveniles) and aspergillosis (3.8% of adults and 7.7% of juveniles).